Persepsi Peserta Didik Tentang Pembelajaran Berdiferensiasi pada Mata Pelajaran Fiqih di MTsN 4 Pasaman Barat - Yona Gus Manita; Charles Charles; Wedra Aprison; Arman Husni (LPPM Universitas 17 Agustus 1945 Semarang, 2024)
Researchers conducted research at MTsN 4 Barat Pasaman which was motivated by the lack of enthusiasm for learning students and learning that was not optimal, the presence of students who did not concentrate on learning, did not understand in this latest learning, namely differentiated learning, some students felt burdened because they were used to being given material from teachers. The purpose of this study is to find out how students' perceptions of the implementation of learning differentiate in fiqh subjects. This type of research is quantitative research with a descriptive approach. The subjects in this study were Class VII students at MTsN 4 Barat Pasaman. While the object of this study is the perception of students about the implementation of differentiated learning in class VII fiqh subjects at MTsN 4 Barat Pasaman. Data collection techniques use questionnaires and documentation, while data analysis techniques use the Percentage formula and the mean formula. From the results of research and data analysis, the author can conclude that students' perceptions of differentiated learning in Fiqh subjects in MTsN 4 Barat Pasaman, reached a score of 887 with the category